1975
DOI: 10.1007/bf00417037
|View full text |Cite
|
Sign up to set email alerts
|

Erfahrungen mit der dynamischen Kompressionsplatte (DCP) bei 418 frischen Unterschenkelschaftbr�chen

Abstract: A consecutive series of 435 fresh fractures of the tibial shaft was internally fixed by the new dynamic compression plate (ASIF-DCP). All but 2 cases could be reviewed personally within 1--2 years postoperatively, while 15 patients had died. The functional results and postoperative complications are reported separately for the 334 closed and 101 open fractures. Inspite of a higher rate of complications in the open fractures, their functional results were about as good as in the closed cases. In our experience … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1986
1986
1992
1992

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…The complication rate following the internal fixation of fractures using plates is small. In a well-documented series of 323 closed/95 open fractures, Rtiedi et al [15] found 3/11 cases with infection, 3/5 cases with pseudarthrosis, 4/7 implant or fixation failures, and 1/1 refractures. A recent review of the same group showed a refracture rate of less than 2% [9].…”
Section: Discussionmentioning
confidence: 99%
“…The complication rate following the internal fixation of fractures using plates is small. In a well-documented series of 323 closed/95 open fractures, Rtiedi et al [15] found 3/11 cases with infection, 3/5 cases with pseudarthrosis, 4/7 implant or fixation failures, and 1/1 refractures. A recent review of the same group showed a refracture rate of less than 2% [9].…”
Section: Discussionmentioning
confidence: 99%